(untitled) (Medico Legal Update, 2024)
Suicide is one of the major global health issues specially in countries having low to medium socioeconomic condition. Hanging is method of choice for adults to commit suicide. Near hanging defined as person who survive a hanging injury for enough time to reach hospital. Tentative cut or self-inflicted injury is an intentional and direct injury to own’s body part. It is also known as self-harm, self-wounding, moderate self-mutilation and parasuicide. Various factors responsible for high mortality in near hanging are low systolic blood pressure (<90), injury severity score (ISS) >15, Glassgow coma scale (GCS) <8, hypoxic brain injury on CT scan. Immediate arrival to hospital and aggressive management of near hanging and its complication can improve the final outcome.